Evaluasi Program Pembiasaan Shalat pada Anak Usia Dini Berdasarkan Model CIPP di TK ‘Aisyiyah Bunda ‘Aisyah - Cahya Kusumajati (Jurnal Pendidikan Indonesia, 2025)
In the reality of this modern era, many children entering adolescence stage do not know the procedures for performing prayers, and even many people still ignore the command to pray. Based on this phenomenon, there is a reason for the need to accustom children to prayer from an early age. This study aims to analyse the implementation, effectiveness, and factors hindering and supporting the smoothness in the implementation of the Early Childhood Prayer Habituation Program at ‘Aisyiyah Bunda ‘Aisyah Kindergarten. It used a qualitative approach through an evaluation research. The data obtained were through interviews, observations, and documentation, which were analysed by steps of reduction, presentation, and verification. Purposive sampling or snowball sampling was used for informant determination. The results of the study showed that first the implementation of the prayer habit program was divided into three stages: the planning stage carried out at the beginning of each new semester and written in the lesson plan every day, the implementation carried out in three flows: ablution, dhuha and dzuhur prayers in congregation, and ended with dhikr and praying together and evaluation carried out weekly via WhatsApp  and reported every semester through report cards. Second, the effectiveness of the prayer habit program was stated to be effective with a range of 70% -90% and third, the inhibiting factors were the conditioning of time and children, changing moods, introduction of the importance of prayer, and the large number of children was not comparable to the number of teachers and the supporting factors were the consistency of introducing prayer in class, teacher cooperation and positive support from parents. Fourth, the results of the CIPP evaluation on the program were stated to be good, indicating that the program must be continued.